2010
DOI: 10.5194/amt-3-51-2010
|View full text |Cite
|
Sign up to set email alerts
|

Four Fourier transform spectrometers and the Arctic polar vortex: instrument intercomparison and ACE-FTS validation at Eureka during the IPY springs of 2007 and 2008

Abstract: Bruker 125HR are shown to agree to within 3.5% with the existing Environment Canada Bomem DA8 measurements. After smoothing both of these sets of measurements to account for the lower spectral resolution of the University of Waterloo Portable Atmospheric Research Interferometric Spectrometer for the Infrared (PARIS-IR), the measurements were likewise shown to agree with PARIS-IR to within 7%. Concurrent measurements of these gases were also made with the satellite-based Atmospheric Chemistry Experiment Fourier… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 29 publications
5
33
0
Order By: Relevance
“…PEARL is strategically located for Arctic studies, as well as the validation of satellite measurements (e.g. Batchelor et al, 2010;Adams et al, 2012). Validating the accuracy of PEARL water vapour measurements thus has substantial value.…”
Section: Measurement Sitementioning
confidence: 99%
“…PEARL is strategically located for Arctic studies, as well as the validation of satellite measurements (e.g. Batchelor et al, 2010;Adams et al, 2012). Validating the accuracy of PEARL water vapour measurements thus has substantial value.…”
Section: Measurement Sitementioning
confidence: 99%
“…The inclusion of criteria ensuring that similar air masses are sampled with respect to the polar vortex reduces this difference seen in the Arctic significantly. Using these additional criteria, Batchelor et al (2010) and Fu et al (2011) found much improved mean differences, between the ACE-FTS (v2.2+updates) and ground-based FTS datasets, for O 3 , HCl, HNO 3 , and HF comparisons by approximately a factor of 2. These mean differences are comparable to the typical differences at lower latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…All of these trace gases are routinely derived from the Bruker 125HR spectra and have been used in numerous studies (e.g., Batchelor et al, 2009;Lindenmaier et al, 2010Lindenmaier et al, , 2011Viatte et al, 2014;Holl et al, 2016). Retrievals of O 3 , HCl, HNO 3 , HF, N 2 O, CO, and C 2 H 6 from PARIS-IR's spectra have also been published and compared to other instruments in previous studies (e.g., Sung et al, 2007;Wunch et al, 2007;Batchelor et al, 2010;Fu et al, 2011;Griffin et al, 2013;Franco et al, 2016). The PARIS-IR CH 4 columns are presented for the first time in this study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations